Análise da concentração do mercado varejista alimentar de autosserviço brasileiro entre 2012 e 2016 - Barbosa Filho, Benedito Alves (2018)
This work aims to explore the market concentration in the Brazilian food retailing industry between 2012 and 2016. It was collected data from the Brazilian Association of Supermarkets (ABRAS) available at the Ranking ABRAS/SuperHiper of the 100 largest food retailers in revenue sales that operated in Brazil during the period above mentioned. Three usual market concentration metrics were calculated for this analysis: Market share, concentration ratio and Hirschman-Herfindahl index (HHI). The market in question is moderately concentrated by these indexes; however, when compared with other countries, it is relatively low. The results also showed that this market experienced a reduction in market concentration between 2012 and 2016